Corporate Governance and Social Media : A Brave New World for Board Directors - Chaher, Santiago; Spellman, James David (World Bank, Washington, DC, 2014)
Publication of secret diplomatic cables through Wikileaks shocked governments and provided a sudden wake-up call to all who thought they were safe from the new power of social media. Consequences went well beyond mere embarrassment; they helped spark the first 'Arab spring' uprising in Tunisia, and other forms of social media helped sustain popular dissent elsewhere in the Middle East and North Africa region. What quickly became obvious is that communications online had a demonstrated a new capacity to upend political agendas everywhere. Widespread use of social media has equal potential to transform corporate agendas. Tools used at Tahrir Square are also available in the capital market for use by directors as much as by disgruntled employees, by consumers both satisfied and aggrieved, by competitors, and by shareowners both retail and institutional in confrontations with the board. By the same token, though, corporations can use social media channels creatively to improve stakeholder loyalty, and improve performance. Corporations can develop new means of constructive dialogue with different constituencies. Benefits might include early warning of threats, identification of new ideas, and amplified means of responding. New communication channels can be a force multiplier and a risk management tool to advance the interests of the business. Still, corporate governance and social media are trends newly met, and market participants are only at the very beginning of a learning curve. Santiago Chaher and James David Spellman do a powerful service by providing a forensic analysis of how social media work. The authors sketch out latest developments. Then they focus on what a forward-thinking board needs to know to ensure that the company is ready to manage the risks and take full advantage of the opportunities presented by social media. Part of the challenge is for individual directors to educate themselves about social media from technology to terminology. They need to know the right questions to ask to test whether the firm is leading or being led. They need to investigate how all the various stakeholders the company affects are using social media. And, most importantly, they have to understand that this is an ongoing, not a one-off, learning process.